2012
DOI: 10.1007/s10068-012-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of various extracts from an edible mushroom Pleurotus eous

Abstract: Pleurotus eous is a pink edible oyster mushroom cultivated in Coimbatore. The aim of present study was to evaluate antioxidant potential of ethyl acetate, methanol, and hot water extracts from P. eous using various in vitro ROS/RNS generated chemical and biological models. Results demonstrated that the graded-dose (2-50 mg/mL) of various extracts markedly scavenged the DPPH, ABTS, and hydroxyl radicals, and showed metal chelating ability, reducing capacity in Fe 3+ /ferricyanide complex, and ferric reducing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 30 publications
5
51
3
Order By: Relevance
“…The total flavonoid content was 2.11 ± 0.19 and 1.26 ± 0.17 mg/g of extract, respectively. It was documented that major components of mushroom extract are phenolics and Pleurotus species exhibited different contents of total phenolic ranging from ~2 to >30 mg/g of extract [27,37,49]. In comparison with our earlier study [28], the results obtained for non-enriched mushrooms were slightly higher.…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentscontrasting
confidence: 77%
See 2 more Smart Citations
“…The total flavonoid content was 2.11 ± 0.19 and 1.26 ± 0.17 mg/g of extract, respectively. It was documented that major components of mushroom extract are phenolics and Pleurotus species exhibited different contents of total phenolic ranging from ~2 to >30 mg/g of extract [27,37,49]. In comparison with our earlier study [28], the results obtained for non-enriched mushrooms were slightly higher.…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentscontrasting
confidence: 77%
“…It has been reported that mushrooms contain different compounds of phenolics. Some authors have stated that mushrooms contain mainly phenolics acids [7,50], while others reported a high amount of flavonoids in extracts [5,37,51]. The total flavonoid content in different species of Pleurotus was found at the level from 1.2 to 2.9 µg/g of extract [49], even to 7.79 mg/g of extract [37].…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentsmentioning
confidence: 96%
See 1 more Smart Citation
“…The amount of total condensed tannins in cap aqueous extract was higher (3.26 ± 0.07 mg catechin/g extract) while stipe methanolic extract showed the lowest amount (1.23 ± 0.01 mg catechin/g extract). Sudha et al (2012) also reported that total flavonoid content of various extracts of Pleurotus eous varied considerably from 6.38-7.79 mg CAE/g extract. Ascorbic acid in the mushroom sample extracts are shown in Fig.…”
Section: Condensed Tannin and Ascorbic Acid Contentmentioning
confidence: 93%
“…The reducing powers of methanolic and aqueous extracts of cap were 0.34 ± 0.004 and 0.54 ± 0.005, respectively at 25 mg/mL concentration. The reducing powers of methanolic and aqueous extracts of Pleurotus eous were reported to be 0.587 and 0.673 at 2.0 mg/mL, respectively (Sudha et al, 2012), however, cap and stipe methanolic extracts of Hypsizygus ulmarius and Calocybe indica were 2.46, 2.53, 1.71 and 2.05, respectively (Babu and Rao, 2013).The high reducing power exhibited by the extracts might be indicative of the hydrogen donating ability of the active species present in the extracts.…”
Section: Reducing Powermentioning
confidence: 99%